2016
DOI: 10.1016/j.jclepro.2015.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Renewing environmental certification in times of crisis

Abstract: The certification of environmental management systems based on international meta-standards such as ISO 14001 and the Eco Management and Audit Scheme has become one of the most common environmental practices. Nevertheless, the financial and economic difficulties faced by many organizations raise the issue of certification renewal and may have an impact on the trends toward decertification recently observed, notably in the case of the later standard. Surprisingly, this issue remains almost unexplored in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 77 publications
1
49
0
1
Order By: Relevance
“…These findings are confirmed by Daddi et al (2014), who found out that the introduction of specific measures in order to facilitate access to ISO 14001 and EMAS moderately increases the number of certified firms [21]. An important aspect to consider is that these measures should be effective in the long run (such as tax incentives) in order to avoid abandonments after obtaining the incentive [53,61]. For small organizations, financial support together with simplification measures have a great impact and foster the maintenance of the registration [41,56,62].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These findings are confirmed by Daddi et al (2014), who found out that the introduction of specific measures in order to facilitate access to ISO 14001 and EMAS moderately increases the number of certified firms [21]. An important aspect to consider is that these measures should be effective in the long run (such as tax incentives) in order to avoid abandonments after obtaining the incentive [53,61]. For small organizations, financial support together with simplification measures have a great impact and foster the maintenance of the registration [41,56,62].…”
Section: Discussionmentioning
confidence: 72%
“…Small firms are often reported as the category which faces major difficulties implementing EMSs [59], and this is mainly due to the lack of human and financial resources to invest [17,18,41,60]. Additionally, they are driven by a short-term orientation that does not allow the exploitation of the advantages of sustainability investments, which generally have a long-term payoff [53,59]. Other significant issues identified concern the lack of customers' interest in the EMS and the lack of recognition by public institutions [17,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of quality management system was also researched [10][11][12][13] and the supervision of inspection and certification bodies was discussed [14][15][16]. Other standards and certifications were also explored [17][18][19][20]. Also, cartels and clubs, resource dependent and new institutionalism theories were used to explain the reasons for the widespread registration of standards [21].…”
Section: Introductionmentioning
confidence: 99%
“…Following the work by Boiral [23], other more recent works have focused in a more or less direct way on the study of the diverse adoption of standard-based EMSs [24][25][26][27][28][29][30][31][32][33][34][35]. In general terms these works have highlighted the important influence of the internal sources of motivation for the better internalization of the practices associated with the EMS in the certified organizations.…”
mentioning
confidence: 99%